Dual practice in the health sector: review of the evidence - Hipólito Fátima; Fronteira Inês; Van Lerberghe Wim; Ferrinho Paulo; Biscaia André (BMC, 2004)
Abstract This paper reports on income generation practices among civil servants in the health sector, with a particular emphasis on dual practice. It first approaches the subject of public-private overlap. Thereafter it focuses on coping strategies in general and then on dual practice in particular. To compensate for unrealistically low salaries, health workers rely on individual coping strategies. Many clinicians combine salaried, public-sector clinical work with a fee-for-service private clientele. This dual practice is often a means by which health workers try to meet their survival needs, reflecting the inability of health ministries to ensure adequate salaries and working conditions. Dual practice may be considered present in most countries, if not all. Nevertheless, there is surprisingly little hard evidence about the extent to which health workers resort to dual practice, about the balance of economic and other motives for doing so, or about the consequences for the proper use of the scarce public resources dedicated to health. In this paper dual practice is approached from six different perspectives: (1) conceptual, regarding what is meant by dual practice; (2) descriptive, trying to develop a typology of dual practices; (3) quantitative, trying to determine its prevalence; (4) impact on personal income, the health care system and health status; (5) qualitative, looking at the reasons why practitioners so frequently remain in public practice while also working in the private sector and at contextual, personal life, institutional and professional factors that make it easier or more difficult to have dual practices; and (6) possible interventions to deal with dual practice.